Distribution of FcγR gene polymorphisms among two sympatric populations in Mali: differing allele frequencies, associations with malariometric indices and implications for genetic susceptibility to malaria. (December 2016) - Cherif, Mariama; Amoako-Sakyi, Daniel; Dolo, Amagana; Pearson, Jan-Olov; Gyan, Ben; Obiri-Yeboah, Dorcas; Nebie, Issa; Sirima, Sodiomon; Doumbo, Ogobara; Troye-Blomberg, Marita; Bakary, Maiga
Abstract Background Genetic polymorphisms in the complex gene cluster encoding human Fc-gamma receptors (FcγRs) may influence malaria susceptibility and pathogenesis. Studying genetic susceptibility to malaria is ideal among sympatric populations because the distribution of polymorphic genes among such populations can help in the identification malaria candidate genes. This study determined the distribution of three FcyRs single nucleotide polymorphisms (SNPs) (FcγRIIB-rs1050519, FcγRIIC-rs3933769 and FcγRIIIA-rs396991) among sympatric Fulani and Dogon children with uncomplicated malaria. The association of these SNPs with clinical, malariometric and immunological indices was also tested. Methods This study involved 242 Fulani and Dogon volunteers from Mali age under 15 years. All SNPs were genotyped with predesigned TaqMan® SNP Genotyping Assays. Genotypic and allelic distribution of SNPs was compared across ethnic groups using the Fisher exact test. Variations in clinical, malariometric and immunologic indices between groups were tested with Kruskal–Wallis H, Mann–Whitney U test and Fisher exact test where appropriate. Results The study confirmed known malariometric and immunologic differences between sympatric Fulani and non-Fulani tribes. Parasite density was lower in the Fulani than the Dogon (p < 0.0001). The mutant allele of FcγRIIC (rs3933769) was found more frequently in the Fulani than the Dogon (p < 0.0001) while that of FcγRIIIA (rs396991) occurred less frequently in the Fulani than Dogon (p = 0.0043). The difference in the mutant allele frequency of FcγRIIB (rs1050519) between the two ethnic groups was however not statistically significant (p = 0.064). The mutant allele of rs396991 was associated with high malaria-specific IgG1 and IgG3 in the entire study population and Dogon tribe, p = 0.023 and 0.015, respectively. Parasite burden was lower in carriers of the FcγRIIC (rs3933769) mutant allele than non-carriers in the entire study population (p < 0.0001). Carriers of this allele harboured less than half the parasites found in non-carriers. Conclusion Differences in the allelic frequencies of rs3933769 and rs396991 among Fulani and Dogon indirectly suggest that these SNPs may influence malaria susceptibility and pathogenesis in the study population. The high frequency of the FcγRIIC (rs3933769) mutant allele in the Fulani and its subsequent association with low parasite burden in the entire study population is noteworthy.